PENILAIAN KONSUMEN TERHADAP PRODUK MUKENA DI BEJI BANGIL PASURUAN: scoring, mukena, artist - Atiqoh, Atiqoh (Buana Pendidikan, 2011)
Beji Bangil mukena is well-known mukena that develops rapidly, in its research it can be done by woman participation. The problem in this research is how consumer think about mukena product, it is a descriptive research and has two subject, there are the artists of this product and the employees in Beji Bangil with 5 artists and consumers in Nizam and Nazar who are buying mukena, with 248 respondents with questionersas its collecting data, data analisis using %, from each artist using process (1) choosing accessories design and pattern (2) choosing materials and its accessories (3) process of sewing and adding accessories (4) finishing technique(5) deciding (6) quality and (7) packing. From consumers research in next step are cheap prices(50%), accessories design (60,30%), trendy (46,37%), color combination (42,33%), its result (44,35%), quality (46,37%) and quite uninteresting (70,96%)